The Exploration of Integration in Guangxi's Orchestral Works during ASEAN Music Week in China：Take "AI GE AI WA" as an example - Yilin, Wang; Jirajarupat, Phakamas; LingLing, Liu (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were 1) To study the fusion of Chinese and Western elements in Guangxi orchestral works. This study is a qualitative research based on the literature research method, and its data comes from various literature materials closely related to the subject of this study. The research results were found as follows; Through more than 10 years of development "China Through more than ten years' development, "China-ASEAN Music Week" has become one of the three important music exchange platforms in China, together with "Beijing Modern Music Festival" and "Shanghai Contemporary Music Week". The purpose of this thesis is to analyze the problems of ethnic integration and diversity in Guangxi orchestral music creation through the study of the work "AI GE AI WA", The fusion of Chinese and Western musical forms and structures represents a significant evolution in orchestral composition, moving beyond the constraints of traditional orchestral works that typically adhere to fixed norms. This innovative blending allows for greater diversity and flexibility in musical expression, enabling composers to explore new creative avenues.